Pengalaman Membangun Cita-Cita serta Tujuan Hidup pada Usia Emerging Adulthood: Analisa Fenomenologi - Lesthari, Fellia; Permana, Muhammad Zein (Jurnal Psikologi Perseptual, 2022)
This study focuses on providing an overview of the experience of building goals and life goals at the age of emerging adulthood at the psychology faculty of UNJANI. This study uses qualitative methods with phenomenological analysis and thematic analysis. Data were collected through in-depth interviews with 3 students who had the characteristics of being at the age of emerging adulthood. The first participant has ideals and goals in life that are unusual/anti-mainstream, the second participant has ideals and goals that fall into the general category, and the third participant has specific goals and life goals. This study found three main themes, namely: 1) success, which means that when asked about the goals and objectives of life, participants described what the definition of ideals and goals in life were, namely success, not about the profession of work but about achievement; 2) the process, namely a person will be more motivated to achieve the ideals and goals of life by increasing self-capacity, not based on the stage of development; 3) nature, namely reaching the ideals and goals of life realistically not based on idealism. The results of the study suggest that a quantitative measuring instrument should be made involving the dimensions of success, process, and nature and realize the importance of the role of religiosity in building life goals and aspirations, the process and mechanism for building ideals, as well as the possible challenges and obstacles that occur.Penelitian ini berfokus untuk memberikan gambaran pengalaman membangun cita-cita serta tujuan hidup pada usia emerging adulthood di fakultas psikologi UNJANI. Penelitian ini menggunakan metode kualitatif dengan analisa fenomenologi dan analisa tematik. Pengambilan data dilakukan melalui wawancara mendalam terhadap 3 orang mahasiswa yang memiliki karakteristik berada pada usia emerging adulthood. Partisipan pertama memiliki cita-cita serta tujuan hidup yang tidak biasa/antimainstream, partisipan kedua memiliki cita-cita serta tujuan yang masuk pada kategori umum, dan partisipan ketiga dengan cita-cita dan tujuan hidup yang spesifik. Penelitian ini menemukan 3 temuan tema utama, yaitu: 1) sukses, yakni artinya ketika ditanya terkait dengan cita-cita serta tujuan hidup, partisipan menggambarkan tentang apa yang menjadi definisi cita-cita serta tujuan hidup, yaitu sukses, bukan soal profesi pekerjaan melainkan soal pencapaian; 2) proses, yakni seseorang akan lebih terdorong untuk mencapai cita-cita serta tujuan hidup dengan meningkatkan kapasitas diri, bukan berdasarkan tahapan perkembangan; 3) sifat, yakni menggapai cita-cita serta tujuan hidupnya dengan realistis bukan berdasarkan idealis. Hasil penelitian menyarankan untuk dibuat alat ukur kuantitatif yang melibatkan dimensi sukses, proses, dan sifat dan menyadari pentingnya peran religiusitas dalam membangun cita-cita serta tujuan hidup, proses dan mekanisme membangun cita-cita, serta kemungkinan tantangan dan hambatan yang terjadi.